Estimation of the size of the black economy in India, 1996-2012 - Arun Kumar (2016)
This article attempts to make an advance in the estimation of the size of the black economy in India by bringing in the institutional aspects of black income generation and taking the macroeconomic variables they affect into consideration. The fiscal approach recognises that black incomes are generated through many different ways in various sectors. The size of the black economy is projected on the basis of the share of the services sector and trade in gross domestic product, with the crime rate representing the extent of illegality. - Reproduced.
Keywords: Black money - India; Black money